unbranded - Glenn Iseger-Pilkington; Travis curtin (2019)
This e-publication accompanied the group exhibition 'unbranded', including Damien Shen, Dean Cross, Gunybi Ganambarr, Illiam Nargoodah, James Tylor, John Prince Siddon, Ngarralja Tommy May, Noŋgirrŋa Marawili, Nyurpaya Kaika Burton, Patrina Munuŋgurr, Sharyn Egan, Sonia Kurarra, Wukun Wanambi at La Trobe Art Institute, Bendigo, from 6 May to 22 June 2019. The exhibition was curated by Glenn Iseger-Pilkington and Travis Curtin. The exhibition presented work by Indigenous contemporary artists whose practices undermine and subvert the notion of a singular Indigenous ‘brand’ or ‘aesthetic’. The paintings, sculptures, photographs, video and installation works unpicked preconceptions of what Indigenous creative practice is or should be, rejecting binary assumptions around ‘traditional/non-traditional’, or ‘urban/remote’ practices and other applied, and often arbitrary categorisations. The exhibition reflected multiplicity, complexity and sometimes-conflicting experiences of culture and identity in contemporary Australia. The publication includes an introduction by Glenn Iseger-Pilkington and Travis Curtin, foreword by Helen Hughes essays by Glenn Iseger-Pilkington and Travis Curtin, a translation of the text-based work of Nyurpaya Kaika Burton, short artists’ biographies and 44 illustrations (colour).